A Consumer Premises End User Interface for OSA/Parlay Applications - Machethe, Thabo (My University, 2007)
The NGN is a multi-service network which inter-works with the Public Switched Telephone Network (PSTN), the voice network and the data network provided by Internet. Through network independent APIs such as OSA-Parlay, the NGN slowly migrates and converges Telecoms and IT networks, voice and Internet, into a common packet infrastructure. The OSA/Parlay group defines a softswitch architecture which provides network independent APIs or SCFs that enable cross network application development The Parlay softswitch provides connectivity to underlying transport networks for application providers. The standard specifies the interaction between application providers and the softswitch. However, the standard does not specify an interface to regulate the interaction between service providers and the consumer/end user domain. This means that applications housed in the service provider domain have no defined interfaces to manage service delivery to the consumer domain. For most service providers, the lack of a non-standardized API set impedes efforts to decrease application creation and deployment time. This research investigates the design and implementation of a standard consumer interface which can be used by application providers within an OSA/Parlay system to deliver service content to end users. The main objectives with regard to the functionality provided by the interface include the integration of facilities which will assist application providers to manage end user access and authentication (to enable users to establish a secure context for service usage), subscription (to handle the subscription life cycle), and service usage management (to enable the initiation and termination of services). The TINA-Consortium (TINA-C) has developed a service architecture to support the creation and provisioning of services in the NGN. The TINA architecture offers a comprehensive set of concepts and principles that can be used in the design of NGN services. The architecture consists of a set of reusable and interoperable service components encapsulating a rich and well defined set of APIs aimed at supporting the interaction between application providers and consumers. TINA’s session concepts, information structures, interfaces and service components can be used to support the design of a consumer premises end user interface for OSA/Parlay. This research also aims to explore the feasibility of using the TINA API within an OSA/Parlay system to support consumer domain service delivery. In order to implement the consumer interface for Parlay applications, the ability of the TINA service architecture to provide Access and Authentication management; Subscription and Profile management; and Service Usage management was investigated. The report documents the design and implementation of an OSA/Parlay consumer interface utilizing TINA service components and interfaces.
Student Number : 9812990V - MSc project report - School of Electrical Engineering - Faculty of Engineering and the Built Environment
Keywords: NGN; multi-service network; Public Switched Telephone Network; PSTN; IT networks; TINA-Consortium; Parlay applications